Designing a Puzzle Game for Delivering the Interactive Learning Material at SMP Kartika 1-7 Padang - Melladia, Melladia; Febriyon Pratama, Vicky; Febri Annisa, Indah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of technology in education has a significant impact on the learning process, including the use of interactive learning media. This study aims to design and implement a puzzle-based game application as a learning aid media at SMP Kartika 1-7 Padang. The main focus of this application is to motivate students and improve their understanding of science subjects through an enjoyable approach. The puzzle game media is designed to address the boredom often experienced with conventional learning methods, such as lectures. The development process uses a phased system development method, which includes needs analysis, design, implementation, and evaluation. This application consists of three main parts: the main menu, level menu, and the game. Each level presents a challenge that encourages students to assemble puzzle pieces to form a complete image, followed by a display of learning material. The use of this application is expected to improve students' concentration, interest, and learning quality by combining educational and entertainment elements. Evaluation results show that this application is effective as a learning media, providing a more interactive learning experience, and can serve as a reference for the future development of technology-based learning media.